Neogene Coal Characteristics and Depositional Environments in the Kikim Area of South Sumatra Basin; Insights from logging, proximate test, sulfur test and electrofacies - Idarwati, Idarwati; Maulia, Dita (Berita Sedimentologi, 2024)
Neogene coal is the main producer in the Kikim area (Gumay Talang District, Lahat Regency) of South Sumatra Basin and is part of the Muaraenim Formation. However, the characteristic and depositional environment of this Neogene coal are still poorly understood. This research was conducted to determine the characteristics and distribution model of coal seams, as well as its depositional environment. Coal seam characteristics include thickness, description, coal rank, depositional structure, and coal seam depositional environment. The methods used in this research are well-logging, proximate and ultimate tests, and electro facies. Geophysical logging analysis was carried out at four drilling points. The results of the analysis from well logging found four seams in order from youngest to oldest seam, namely seam B, seam C, seam D, and seam E. Seam B has the most significant thickness, namely 9.55 meters, Seam C 2.29 meters, seam D 4.90 meters and Seam E 2.10 meters. The ASTM classification shows that the coal seam is included in the coal rank Sub-bituminous B – Sub-bituminous A. The determination of coal rank uses the ASTM D-388 classification, which aims to identify the coal grade. The parameters used in determining coal rank are fixed carbon content, calorific value, and volatile matter. The depositional structure found at the research location is split. The depositional environment interpretation of coal seams uses three parameters lithofacies, sulphur content and electro facies. Our research revealed that the study area's depositional environment is in the upper delta plain in the backswamp-floodplain section.